Long-term crop productivity response and its interaction with cereal markets and energy prices. (April 2019) - Thompson, Wyatt; Dewbre, Joe; Pieralli, Simone; Schroeder, Kateryna; Pérez Domínguez, Ignacio; Westhoff, Patrick
Highlights: Crop yield response to price is critical for long-run food policy analysis. Yield response tends to be higher in developed countries than developing countries. Energy shock implications for cereal prices diminish with long-run yield response. Abstract: Crop yields are endogenous as long as economic agents adjust to permanent changes in expected prices. The literature, however, does not offer a definitive value of how much yield would change in response to sustained price changes. To fill the gap, we use available scientific findings and data to estimate yield elasticities that enable agricultural commodity and food policy analysis. Using a world market model with short- to long-run yield response, we show the impacts of sustained energy price shocks on global cereal supply and demand. The results highlight substantial differences in quantity and price effects depending on the yield elasticities. These results demonstrate the need to recognize yield response when assessing impacts of energy prices or biofuel production on food uses or, more generally, on food security in the face of income and population growth, evolving dietary patterns, climate change implications, or other long-run pressures.